RISKS IN THE MANAGEMENT OF INVESTMENT PROJECTS OF INTEGRATED ENTREPRENEURIAL STRUCTURES IN UKRAINE (INNOVATIVE ECONOMY, 2026)
Fedoryshyna L.M., Izhevskyi P.H., Ursol V.I. RISKS IN THE MANAGEMENT OF INVESTMENT PROJECTS OF INTEGRATED Entrepreneurial STRUCTURES IN UKRAINEPurpose. The aim of the article is to determine approaches to the management of investment projects of integrated entrepreneurial structures of Ukraine in the context of six key industries – agro-industrial complex, logistics, retail, medical business, information technologies and residential construction – in the context of existing risks and industry specifics.Methodology of research. A set of general scientific and special research methods was used to achieve the set goal, enabling a systematic analysis of investment project management under martial law conditions: system analysis was employed to form a target sample of leading integrated entrepreneurial structures in Ukraine representing six key industries; the synthesis method was used to combine various theoretical approaches and formulate the author's definition of the concept of an “integrated entrepreneurial structure project”; the systematization method was applied to present a classification of investment projects according to funding volumes, integration types, and participants, as well as to group the main types of risks by industry sector; comparative analysis was used to examine the structure of investment resources and identify differences in financing sources across various industries; the graphical method was employed to develop and visualize a decision-making framework for selecting an appropriate form of participation in residential construction projects based on a company's risk profile.Findings. It is substantiated that effective investment project management is a strategic factor in ensuring the resilience of large businesses under martial law conditions. The author's interpretation of the concept of an “integrated entrepreneurial structure project” is proposed. The investment activity of leading Ukrainian companies across six key industries was analysed, confirming a significant increase in funding for modernization programs during 2024–2025. The forms of company participation in residential construction projects were systematized, and on this basis, a framework for selecting an appropriate form of participation according to a company's risk profile was proposed. The dynamics of key indicators of Ukraine’s residential construction sector over the past five years were presented. The main types of risks associated with investment projects implemented by integrated entrepreneurial structures in Ukraine were identified and described, revealing their pronounced industry-specific differentiation. It was found that a shift from rigid hierarchical integration toward network-based models characterized by “weak ties” contributes to a more effective distribution of risks among project participants.Originality. The study of approaches to managing investment projects of integrated entrepreneurial structures of Ukraine in the context of certain industries (agro-industrial complex, logistics, retail, medical business, information technologies and residential construction) received further development. This made it possible to formulate the author's interpretation of the concept of an “integrated entrepreneurial structure project”, identify the key risks associated with investment projects, and determine the structure of investment resource sources used to finance these projects under martial law conditions.Practical value. The findings of the conducted research can become the foundation for further scientific research aimed at identifying effective approaches to minimizing risks in investment project management. In addition, they can be utilized by the management of integrated entrepreneurial structures to transform investment strategies from a “survival mode” approach to a model of proactive growth and international expansion.Key words: integrated entrepreneurial structures, investment projects, project risks, agro-industrial complex, logistics, healthcare, information technology (IT), residential construction, sources of investment resources, war-related risks, strong integration, weak ties.
Keywords: integrated entrepreneurial structures; investment projects; project risks; agro-industrial complex; logistics; healthcare; information technology (IT); residential construction; sources of investment resources; war-related risks; strong integration; weak ties